I met a moose in Maine one day - Shankman, Ed.; O'Neill, Dave (Beverly, Mass. : Commonwealth Editions, 2008)
A young boy and a moose go on a fun-filled tour of the state of Maine.
Keywords: Boys -- Juvenile fiction; Moose -- Juvenile fiction; Maine -- Juvenile fiction